2019
DOI: 10.1038/s41598-019-39362-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hepatocellular lipid accumulation and energy metabolism in patients with long standing type 1 diabetes mellitus

Abstract: The prevalence of obesity and metabolic syndrome increases in patients with type 1 diabetes mellitus (T1DM). In the general population this is linked with ectopic lipid accumulation in liver (HCL) and skeletal muscle (IMCL), representing hallmarks in the development of insulin resistance. Moreover, hepatic mitochondrial activity is lower in newly diagnosed patients with T1DM. If this precedes later development of diabetes related fatty liver disease is currently not known. This study aims to investigate energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Using 1 H/ 31 P magnetic resonance spectroscopy (MRS), cross-sectional analyses demonstrated higher hepatocellular lipid (HCL) content in T2DM, but lower hepatic adenosine triphosphate (γATP) and inorganic phosphate (Pi) concentrations in both T2DM and T1DM compared with glucose tolerant persons [7][8][9] . Subsequent studies revealed that higher HCL relates to upregulated mitochondrial respiration and increased acetyl-CoA flux 10 , whereas 13 C MRS found no alterations of hepatic mitochondrial oxidation at least in non-obese NAFLD 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Using 1 H/ 31 P magnetic resonance spectroscopy (MRS), cross-sectional analyses demonstrated higher hepatocellular lipid (HCL) content in T2DM, but lower hepatic adenosine triphosphate (γATP) and inorganic phosphate (Pi) concentrations in both T2DM and T1DM compared with glucose tolerant persons [7][8][9] . Subsequent studies revealed that higher HCL relates to upregulated mitochondrial respiration and increased acetyl-CoA flux 10 , whereas 13 C MRS found no alterations of hepatic mitochondrial oxidation at least in non-obese NAFLD 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Over time, complications develop in patients with type 1 DM (T1DM), which are closely related to dysfunction in energy metabolism and insulin resistance [3]. The liver is a key metabolic organ which regulates corporeal energy metabolism, with a previous study indicating that T1DM reduces the hepatic energy metabolism activity [4]. Meanwhile, the hepatic AMP-activated protein kinase (AMPK) and insulin signaling pathway are known to perform an integral role in maintaining the energy status [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Three reported LFC as continuous measure and found significantly lower LFC in groups of less than 20 patients compared to age-and BMI matched controls. [15,16,36] All three studies reported quite low LFC values in patients as well as in the control populations. These large discrepancies of NAFLD prevalence in MRI studies compared to ours may be explained by differences in study population, sample size and patient selection, as well as by measurement techniques.…”
Section: Discussionmentioning
confidence: 91%
“…Six additional studies assessed liver fat content (LFC) by MRI techniques. [15,16,[33][34][35][36] Three defined NAFLD as an LFC of more than 5.5%, which is comparable to a CAP stage of S1 or higher, and reported prevalence rates ranging from 0.0 to 8.8%. [33][34][35] Three reported LFC as continuous measure and found significantly lower LFC in groups of less than 20 patients compared to age-and BMI matched controls.…”
Section: Discussionmentioning
confidence: 99%